MEDIEVAL KHOREZM CRAFTSMANSHIP: HISTORY OF STUDY AND RESEARCH PROSPECTS - Abdullaev Timur (Scholars Digest Publishing, 2025)
The study of medieval Khorezm craftsmanship explores the rich history of artistic and artisanal traditions in the Khorezm region, highlighting its cultural and economic significance. Research in this field has evolved over time, with scholars examining archaeological findings, historical texts, and preserved artifacts to understand the techniques, materials, and socio-cultural contexts of craftsmanship. Key areas of focus include pottery, metalwork, textiles, and architecture, which reflect the region's unique blend of local and foreign influences. Despite significant progress, many aspects of Khorezm's craftsmanship remain underexplored, offering promising avenues for future research. This article reviews the history of studies on Khorezm craftsmanship and outlines potential directions for further investigation.
Keywords: Khorezm, craftsmanship, medieval, archaeology, pottery, metalwork, textiles, architecture, cultural history, research prospects.